Infections related to health care in adult intensive care units of adult hospitals: integrative review - Santos, Lauro Ricardo de Lima; de Almeida Neto, Omar Pereira; de Freitas, Efigênia Aparecida Maciel (Journal of Health Care, 2016)
Introduction: Intensive Care Units (ICU) are places for the recovery of critically ill patients. However, high rates of infection are still prevalent in this area. Objective: To find in the literature studies characterizing the profile of health care associated infections (HAIs) in adult ICUs of university hospitals. Methodology: integrative literature review using the descriptors "university hospital/hospitais universitários", "critical care unit/unidade de terapia intensiva", and "nosocomial infections/infecção hospitalar" linked by the Boolean operator "AND" in the PUBMED database (US National Library of Medicine), LILACS (Latin American and Caribbean Health Sciences Literature) in the Virtual Health Library Research Portal, and Scientific Electronic Library Online (SciELO). Articles published between 2010 and 2015, available in full, in Portuguese, Spanish, and English were considered. Results: We found 397 articles, but after filters only four articles were included in this integrative review, 2 from the PUBMED database, 1 in LILACS, and 1 in SCIELO, performed in Cuba, Brazil, Colombia, and China. Most (n=3) of these were published in 2011. The proposed methodologies were prospective studies, quantitative, descriptive, and observational. Most studies (75%) were conducted by doctors, one of them a specialist epidemiologist. Conclusions: The main HAIs found in ICUs were ventilator associated pneumonia (VAP), followed by Bloodstream infection (BSI), and urinary tract infection (UTI). Knowing this profile can colaborate with staff and supervisory bodies training, reducing morbidity and mortality.